2018
DOI: 10.1021/acs.est.8b02740
|View full text |Cite
|
Sign up to set email alerts
|

Defect Sites in Ultrathin Pd Nanowires Facilitate the Highly Efficient Electrochemical Hydrodechlorination of Pollutants by H*ads

Abstract: Adsorbed atomic H (H*) facilitates indirect pathways playing a major role in the electrochemical removal of various priority pollutants. It is crucial to identify the atomic sites responsible for the provision of H*. Herein, through a systematic study of the distribution of H* on Pd nanocatalysts with different sizes and, more importantly, deliberately controlled relative abundance of surface defects, we uncovered the central role of defects in the provision of H*. Specifically, the H* generated on Pd in an el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 43 publications
5
128
2
1
Order By: Relevance
“…In this regard, Pd distinguishes itself not only for its high efficiency in taking up protons to generate H* but also due to its property to retain the H* by adsorption onto the Pd surface (H* ads ) and absorption to the Pd atoms via the formation of Pd hydride (H* abs ). 220 Therefore, Pd can maintain a high surface hydrogen concentration for the ECH process. In most of the cases, it is difficult for other materials (e.g., Pt, Rh) to retain the generated H* ads , since the H* ads are easily transform to molecular hydrogen through the Heyrovsky step or the Tafel step.…”
Section: Electroreductive Dehalogenation Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Pd distinguishes itself not only for its high efficiency in taking up protons to generate H* but also due to its property to retain the H* by adsorption onto the Pd surface (H* ads ) and absorption to the Pd atoms via the formation of Pd hydride (H* abs ). 220 Therefore, Pd can maintain a high surface hydrogen concentration for the ECH process. In most of the cases, it is difficult for other materials (e.g., Pt, Rh) to retain the generated H* ads , since the H* ads are easily transform to molecular hydrogen through the Heyrovsky step or the Tafel step.…”
Section: Electroreductive Dehalogenation Mechanismsmentioning
confidence: 99%
“…Recently, several effective methods have been applied to further enhance the selectivity of Pd. 190,220 For example, Liu and co-workers 220 found that the defective sits in Pd nanowires could enhance the stability of the generated H* ads and suppress the HER process. Due to the magnificent H* ads generation/provision capacity, the defect-rich Pd nanowires exhibited a higher 2,4dichlorophenol removal efficiency with a six-times-lower Pd loading than the unmodified Pd materials.…”
Section: Electroreductive Dehalogenation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of atomic hydrogen H * on Pd is of crucial importance as adsorbed H * (H * ads ) is the only active hydrogen species in catalytic hydrodechlorination reactions (Jiang et al 2017;He et al 2018;Liu et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Among the different hydrogen species, i.e. H * abs , H * ads and H 2 bubbles, H * ads is the only active hydrogen species in the catalytic hydrodechlorination process (Jiang et al 2017;He et al 2018b), and the presence of defects on Pd surface facilitates the efficient hydrodechlorination by H * ads (Liu et al 2018). Another beneficial effect of this metal is the production of a smaller number of reaction intermediates, especially low chlorinated compounds such as DCE isomers and vinyl chloride (Zhang et al 1998;Lowry and Reinhard 1999).…”
Section: Polymetallic Particlesmentioning
confidence: 99%